Hydroxyethyl Starch Nanocapsules by Multiple Nanoemulsions for Carrying and Controlled Release of Lapachol - Casagrande-Denardin, J (Elsevier B.V., 2020)
In the present work, an alternative to synthesized nanocapsules in which the lipophilic core was a multiple nanoemulsification forming a complex system constituted of various phases was studied. A primary emulsion (O/W) was poured into another lipophilic solvent, forming a multiple nanoemulsion (O/W/O) able to provide the encapsulation of lapachol, a lipophilic drug. The synthesized nanocapsules were well characterized and the results demonstrate a core-shell morphology, based on the polyurethane formation that exists in the cross-linked starch shell. Furthermore, these systems have moderate stability, with particle size measuring up to 274 nm. The nanocapsules containing lapachol encapsulated 73% of the drug initially added. This demonstrates success in the synthetic route adopted, evidenced by the efficiency of incorporation of the lapachol, in addition of providing a controlled release, reaching 51.4% in 24 h. This behavior shows that the polymeric shell influences the drug release profile and it is in accordance with the kinetic model proposed by Peppas. © 2020